FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUASAN PENGUNJUNG KEBUN RAYA MANGROVE GUNUNG ANYAR SURABAYA - Laraswari, Ananda Nabila; Soedarto, Teguh; Yuliati, Nuriah (Lambung Mangkurat University-Indonesia, 2025)
The Mangrove Botanical Garden of Gunung Anyar is the first and only thematic Mangrove Botanical Garden in Indonesia. Covering a total area of 34 hectares, the Mangrove Botanical Garden of Gunung Anyar houses 59 types of mangrove plants. In 2024, there was a decline in visitor numbers, possibly due to the implementation of entrance tickets which were previously not enforced or were free. This change has prompted many visitors to reconsider visiting the Mangrove Botanical Garden of Gunung Anyar. The aim of this study is to analyze the factors influencing visitor satisfaction levels at the Mangrove Botanical Garden of Gunung Anyar. Quantitative data analysis was conducted using SEM-PLS through the Warp-PLS 7.0 application with four variables: service quality, price, facilities, and destination image. In this analysis, researchers collected and processed data from questionnaires distributed to visitors, assigning weights to each Likert scale response. The research findings indicate that service quality has a coefficient path of 0.03 and a significance of 0.36, showing a positive but not significant effect on visitor satisfaction, thus rejecting the hypothesis. Meanwhile, the influence of price, facilities, and destination image on visitor satisfaction demonstrates a positive and significant impact with a significance value of <0.01, thereby accepting the hypothesis. Destination image has the most significant impact on visitor satisfaction, with a path coefficient of 0.48, and the most influential indicator being unique destination image with a path coefficient of 0.897.